Europe's radical left : from marginality to the mainstream? - March, Luke HerausgeberIn; Keith, Dan HerausgeberIn; The University of Edinburgh (Rowman & Littlefield International, 2016)
Radical left "success" before and after the great recession : still waiting for the great leap forward? / Luke March -- Capitalist crisis or crisis of capitalism? : how the radical left conceptualises the crisis / David J. Bailey -- Uplifting the masses? : radical left parties and social movements during the crisis / Oscar García Agustín & Martin Bak Jørgensen -- The radical left and immigration : resilient or acquiescent in the face of the radical right? / Francis McGowan and Daniel Keith -- The French radical left and the crisis : "business as usual" rather than "le grand soir" / Fabien Escalona and Mathieu Vieira -- Ideological confirmation and party consolidation: Germany's Die Linke and the financial and refugee crises / Amieke Bouma -- Failing to capitalise on the crisis : the Dutch Socialist Party / Daniel Keith -- The Icelandic left-green movement from victory to defeat / Silja Bára Ómarsdóttir and Andrés Ingi Jónsson -- Struggling for coherence : Irish radical left and nationalist responses to the austerity crisis / Richard Dunphy -- Czech communists and the crisis : between radical alternative and pragmatic Europeanization / Vladimír Handl and Andreas Goffin -- Latvia's "Russian left" : trapped between ethnic, socialist, and social-democratic identities / Ammon Cheskin and Luke March -- The Portuguese radical left and the great recession : old challenges and new responses / André Freire and Marco Lisi -- The left and the crisis in Cyprus : "in the midst of change they do not change" / Gregoris Ioannou and Giorgos Charalambous -- Greek radical left responses to the crisis : three types of political mobilisation, one winner / Costas Eleftheriou -- Riders on the storm : united left and Podemos during the 2008 great recession / Luis Ramiro -- To EU or not to EU? : the transnational radical left and the crisis / Michael Holmes and Simon Lightfoot -- Conclusion : the European radical left : past, present, no future? / Daniel Keith and Luke March